Dermal cylindroma of the external auditory canal - Vivek Dokania; Indranil Mukherjee (University of São Paulo, 2023)
External auditory canal (EAC) cylindroma is a rare tumor that mainly presents as a painless mass over the lateral aspect of the ear canal. They have been designated under different nomenclatures in the literature, and controversies persist about their etiology and histogenesis. Moreover, a clinical diagnosis of EAC cylindroma is often challenging because of their rarity and a close resemblance with other adnexal benign and malignant tumors. None of the previous authors have extensively reviewed the dermal cylindroma of the EAC. We provide an extensive review involving PubMed and Google Scholar and report by Preferred Reporting Items for Systematic Reviews and Meta-Analyses standards. A total of 8 cases are included in the current study. The mean age is 55.13 years. There are six females and two males. The left and right ear are involved in 62.50% and 37.50% of cases, respectively. The most common sign/symptom is painless mass (50%). Five authors reported a primary lesion (62.50%), while the remaining 3 reported a recurrent tumor (37.50%). Benign versus malignant cylindroma is reported in 87.50% and 12.50% of cases, respectively. All, except one case, reported a solitary swelling. Surgical excision was employed in all the cases. Primary defect closure versus defect closure with local/distant skin graft /flap is utilized in 37.50% and 62.50% of cases, respectively.